Keretapi Tanah Melayu Berhad (KTMB) / Mohd Izwan Awang Sulong and Mohammad Asyraf Mastapa - Awang Sulong, Mohd Izwan; Mastapa, Mohammad Asyraf (2017)
• Case study on KTM Komuter Customer Service at Rawang Railway Station • Vending machine is not well functioning. • Lack of frontliner staffs to help • Long queue to buy token and top up for KTM Komuter link card • Only one 'touch n go' machine available at the KTM Komuter station